AGN impact on the molecular gas in galactic centres as probed by CO lines. Issue 1 (7th February 2022) - Esposito, Federico; Vallini, Livia; Pozzi, Francesca; Casasola, Viviana; Mingozzi, Matilde; Vignali, Cristian; Gruppioni, Carlotta; Salvestrini, Francesco
ABSTRACT: We present a detailed analysis of the X-ray, infrared, and carbon monoxide (CO) emission for a sample of 35 local ( z ≤ 0.15), active ( L X ≥ 10 42 erg s −1 ) galaxies. Our goal is to infer the contribution of far-ultraviolet (FUV) radiation from star formation (SF), and X-ray radiation from the active galactic nuclei (AGNs), respectively, producing photodissociation regions (PDRs) and X-ray-dominated regions (XDRs), to the molecular gas heating. To this aim, we exploit the CO spectral line energy distribution (CO SLED) as traced by Herschel, complemented with data from single-dish telescopes for the low- J lines, and high-resolution ALMA images of the mid- J CO emitting region. By comparing our results to the Schmidt–Kennicutt relation, we find no evidence for AGN influence on the cold and low-density gas on kpc-scales. On nuclear ( r  = 250 pc) scales, we find weak correlations between the CO line ratios and either the FUV or X-ray fluxes: this may indicate that neither SF nor AGN radiation dominates the gas excitation, at least at r  = 250 pc. From a comparison of the CO line ratios with PDR and XDR models, we find that PDRs can reproduce observations only in presence of extremely high gas densities ( n > 10 5 cm −3 ). In the XDR case, instead, the models suggest moderate densities ( n ≈ 10 2−4 cm −3 ). We conclude that a mix of the two mechanisms (PDR for the mid- J, XDR, or possibly shocks for the high- J ) is necessary to explain the observed CO excitation in active galaxies.